Earnings Management and Different Tax Book To Explain Earnings Persistency - Merkusiwati, Ni Ketut Lely Aryani; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi, 2020)
The study aims to test the direct and indirect effects of earnings management on earnings persistence through different tax books. Opportunistic earnings management results can reduced persistence of accruals. A decrease in accrual persistence will reduce earnings persistence. Different book tax variable were added as an alternative explanation. Earnings management can increase the book tax different reported by the company. A high tax different book can also reduce earnings persistence. A high tax different book is a signal of poor earnings quality. The population of this study is companies listed on the Indonesia Stock Exchange. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2012-2018. Data analysis methods used in this study were descriptive statistics and path analysis. The path analysis results prove that there is the indirect effect of earnings management on earnings persistence through different tax books. The results of the study prove that there is no the direct influence of earnings management on earnings persistence. Keywords: Book Tax Different; Earnings Management; Earnings Persistency.